Do You Really Mean It? Assessing the Strength, Frequency, and Reliability of Applicant Commitment Statements During the Anesthesiology Residency Match. (September 2019) - Moran, Kenneth R.; Schell, Randall M.; Smith, Kathleen A.; Abdel-Rasoul, Mahmoud; Lekowski, Robert W.; Rankin, Demicha D.; DiLorenzo, Amy; McEvoy, Matthew D.
Abstract : BACKGROUND: Despite the critical nature of the residency interview process, few metrics have been shown to adequately predict applicant success in matching to a given program. While evaluating and ranking potential candidates, bias can occur when applicants make commitment statements to a program. Survey data show that pressure to demonstrate commitment leads applicants to express commitment to multiple institutions including telling >1 program that they will rank them #1. The primary purpose of this cross-sectional observational study is to evaluate the frequency of commitment statements from applicants to 5 anesthesiology departments during a single interview season, report how often each statement is associated with a successful match, and identify how frequently candidates incorrectly represented commitments to rank a program #1. METHODS: During the 2014 interview season, 5 participating anesthesiology programs collected written and verbal communications from applicants. Three residency program directors independently reviewed the statements to classify them into 1 of 3 categories; guaranteed commitment, high rank commitment, or strong interest. Each institution provided a deidentified rank list with associated commitment statements, biographical data, whether candidates were ranked-to-match, and if they successfully matched. RESULTS: Program directors consistently differentiated among strong interest, high rank, and guaranteed commitment statements with κ coefficients of 0.9 (95% CI, 0.8–0.9) or greater between any pair of reviewers. Overall, 35.8% of applicants (226/632) provided a statement demonstrating at least strong interest and 5.4% (34/632) gave guaranteed commitment statements. Guaranteed commitment statements resulted in a 95.7% match rate to that program in comparison to statements of high rank (25.6%), strong interest (14.6%), and those who provided no statement (5.9%). For those providing guaranteed commitment statements, it can be assumed that the 1 candidate (4.3%) who did not match incorrectly represented himself. Variables such as couples match, "R" positions, and not being ranked-to-match on both advanced and categorical rank lists were eliminated because they can result in a nonmatch despite truthfully ranking a program #1. CONCLUSIONS: Each level of commitment statement resulted in a progressively increased frequency of a successful match to the recipient program. Only 5.4% of applicants committed to rank a program #1, but these statements were very reliable. These data can help program directors interpret commitment statements and assist accurate evaluation of the interest of candidates throughout the match process.